Analysis of Systems for Coordination of Enterprise Subsystems Control (Journal of Universal Science Research, 2024)
Any automated production, at the current stage, must have systems or control modules that serve to coordinate the subsystems of the entire enterprise. Control in this case occurs through the use of separate modules responsible for monitoring each individual subprocess. Software modules are being developed for such processes, which combine monitoring and operational regulation under the processes, which allows to one degree or another to reduce the risk of damage or failure of all production links.   Thus, the creation of a computer-integrated management system for coordinating the functioning of the subsystems of the enterprise is an urgent and timely task. This paper analyzes the basics of building a production subsystem control system. Algorithms for the operation of such systems are also considered.